Upaya Meningkatkan Kemampuan Pemecahan Masalah Matematik Siswa Dengan Menerapkan Model Pembelajaran Problem Based Learning (PBL) Di SMP Negeri 2 Mardingding - Jaka Supan Sakti Sembiring; Asmin Asmin (Departement of Mathematics Education, 2024)
The aim of this study was to enhance students' mathematical problem-solving abilities in class VII of SMP Negeri 2 Mardingding by using a problem-based learning model in the spatial geometry curriculum on the data side. Thirty-two students from SMP Negeri 2 Mardingding's VII-1 class participated in this study. Six of the thirty-two students, averaging fifty-two, completed the initial ability test and satisfied the learning objectives. According to the guidelines for using the learning model, cycle I students' average ability was 64.15, and 13 out of 32 students, or 40.62%, finished the course. In cycle II, 28 students, or 87.5%, finished with an average score of 80.2 out of 32. Based on learning management data, the average ability of educators in cycle I varied from 3.16 to 3.44 in cycle II, with a very excellent category, according to the researcher. It may be said that this research was effective as the Problem Based Learning learning model has succeeded in reaching the classical learning completion objective, as evidenced by the fact that 87.5% of students in this class attained a learning outcome percentage of ≥ 85%.